The study of exchange rates behavior in Malaysia by using NATREX model - Johari, Mohamad Shukri; Habibullah, Muzafar Shah; Yusop, Zulkornain; Lee, Chin (Faculty of Science and Technology, University of El Oued, 2017)
This paper aims to estimate equilibrium exchange rates and identify the determinants of macroeconomics fundamentals affecting exchange rates in Malaysia. By using Natural Real Exchange Rates (NATREX) model, this study adopts the Autoregressive Distributed Lag (ARDL) model to examine the long run relationships (or cointegration) among variables and the dynamic effect within variables in the short run for the period 1970 to 2012. The results suggest that the terms of trade, dependency ratio of the young, and foreign direct investment play an important role in influencing the exchange rates movement in Malaysia. The result also reveals that the misalignment of exchange rates is quite small and stable in Malaysia during 1983 to 2012, except in 1995.